Persepsi Siswa Madrasah Aliyah Rejang Lebong Terhadap Program Studi Komunikasi dan Peyiaran Islam Jurusan Dakwah Stain Curup - Bakti Komalasari; Semarni Sumai; Adinda Tessa Naumi (Institut Agama Islam Negeri (IAIN) Curup, 2017)
The development of STAIN Curup has shown a significant improvement both in terms of the number of students and the institutional aspect. The existence of STAIN Curup began to be felt as part of the world of education not only for the environment but also for the nearest regency areas such as Lubuk Linggau, Kepayang, Lebong, Bengkulu City, Palembang, Bukit Tinggi and even from Java Island. This development is not directly proportional to the growth of the number of new students each year in the Communication Studies and Islamic Broadcasting Program (Prodi KPI), which is still far tertiggal compared with other Prodi-Prodi in STAIN Curup. Therefore, this research tries to find a solution about it, by focusing on two research problems (1) How is the perception of MA students about KPI Study, Department of Propagation, STAIN Curup? (2) What factors influence student's perception about KPI Prodi Major Dakwah STAIN Curup? This research sees information about the KPI Prodi obtained from family / friends / neighbors who are currently or have completed education at STAIN Curup, mass media that is through advertisement acceptance new newspaper Daily Newspaper Radar Pat Petulai, and Radio Pesona FM, and from brochure of student admission new. Then the information will be organized and interpreted. Based on the result of the research, the perception of MAN Curup and MA Ar-Rahmah students toward KPI Study Program of STAIN Curup Dakwah, among others: Prodi KPI is good enough, KPI Prodi still doubt, and not too familiar with Prodi KPI. The formation of MA students' perceptions of KPI study is influenced by several factors. Factors that influence the perception of MA students include: experience, motivation, interests and needs, expectations, and stereotypes.